2020
DOI: 10.1039/d0ee02347g
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the nature of the passivation layer enabling reversible calcium plating

Abstract: As for other multivalent systems, the interface between the calcium (Ca) metal anode and the electrolyte is of paramount importance for reversible plating/stripping. Here, we combined experimental and theoretical approaches...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 47 publications
7
125
0
Order By: Relevance
“…The surface of Ca seems immediately covered by the ionically insulating SEI due to the decomposition of electrolytes. 109 Cross-linked borate polymers are suggested as conducting components for Ca-ion migration. 109 Forming alloy interphases (for example, Ca-Sn alloys) can also protect the Ca anode from the passivation by the electrolytes.…”
Section: Comparison Of Sei Formed On Alkali Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of Ca seems immediately covered by the ionically insulating SEI due to the decomposition of electrolytes. 109 Cross-linked borate polymers are suggested as conducting components for Ca-ion migration. 109 Forming alloy interphases (for example, Ca-Sn alloys) can also protect the Ca anode from the passivation by the electrolytes.…”
Section: Comparison Of Sei Formed On Alkali Metalsmentioning
confidence: 99%
“…109 Cross-linked borate polymers are suggested as conducting components for Ca-ion migration. 109 Forming alloy interphases (for example, Ca-Sn alloys) can also protect the Ca anode from the passivation by the electrolytes. 110 Trivalent metal Al anode with the highest volume-specific capacity (8,040 mAh cm À3 ) also faces sluggish kinetics in traditional electrolytes, which usually undergoes reversible electrochemistry under the highly corrosive ionic liquid (IL) based electrolytes such as the mixture of AlCl 3 and-1-ethyl-3-methylimidazolium chloride (EMImCl).…”
Section: Comparison Of Sei Formed On Alkali Metalsmentioning
confidence: 99%
“…The strong Ca, O curve in the SEI is expected as prior work 7 has shown that a nanoscale oxide is present at the Ca surface. Boron in the SEI has been found in other borate-containing electrolytes 8 and is under further investigation. Extensive detail about the structure and chemistry of the bulk, SEI, and co-depositing hydride phases will be presented.…”
mentioning
confidence: 83%
“…In 2016, reversible Ca plating/stripping was first reported in an electrolyte of Ca(BF 4 ) 2 in ethylene carbonate/propylene carbonate at 100°C 11 . The deposited product contained not only Ca metal but also CaF 2 , which inhibits Ca diffusion and hinders plating and stripping processes 12 .…”
Section: Introductionmentioning
confidence: 99%